RESEARCH OF THE CONCEPT OF PHRASEOLOGY AND THE TYPE OF IDIOMATICITY AND THE MAIN TYPES OF PHRASEOLOGICAL UNITS - Tulaboyeva, Gulorom (Журнал иностранных языков и лингвистики, 2023)
In this article, we will focus on studying the origin of phraseology. In this article, the authors ask about word phraseology and how it differs from lexicology. To understand the word phraseologies, they first introduced scientists who made their first attempts to study the field of linguistics that we call phraseology. As can be seen from his notes, this field of linguistics is very young and few scholars have managed to see the world as phraseology raises it. This article analyzes the main types of expression units related to the idiomatic level in foreign language study. The authors have tried to determine the types of expression units using examples.